Young Adults' Perspectives on the Implications of an Augmented Reality Mobile Game for Communities' Public Health: A Qualitative Study - Yuk Chiu Yip; Ka Huen Yip; Wai King Tsui (Frontiers Media S.A., 2023)
Objectives: Several physical, psychological, and social health consequences are caused by smartphone users' addiction to games. A location-based game (LBG), Pokémon GO, recently garnered significant attention from young people. This study aims to explore their experiences with this game and motivations for playing, investigating their perspectives on the game's implications for themselves and the public health of their communities.Methods: Ten qualitative focus group interviews were conducted. Young adults, aged 18-25 years (n = 60), were recruited in Hong Kong. Data were analyzed using a thematic approach.Results: Five themes emerged: 1) missing out or self-regulation, 2) childhood memories of Pokémon, 3) extending virtual-reality exploration, 4) spending more time outdoors walking and exercising, and 5) getting together with others and social interaction.Conclusions: This study showcases the motivational factors of young adults and their cohorts in societies worldwide. LBGs may impact players' physical and social activity levels, and behavior. Nonetheless, certain negatives were identified (i.e., addiction and behavior resulting from a loss of self-control). These negatives deserve health practitioners' attention and future studies should explore possible public health interventions